1998
DOI: 10.1063/1.121056
|View full text |Cite
|
Sign up to set email alerts
|

Origin of conductivity and low-frequency noise in reverse-biased GaN p-n junction

Abstract: Simultaneous low-frequency noise characterization of gate and drain currents in AlGaN/GaN high electron mobility transistorsLow-frequency noise in AlGaN/GaN heterojunction field effect transistors on SiC and sapphire substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 12 publications
5
44
0
Order By: Relevance
“…This value corresponds to the ionization energy of the generation level, which is attributed to the donor defect level introduced during the MOCVD growth. However, the high reverse dark current and the larger resistance observed in the device may be attributed to the density of dislocations remaining in the film [16,17]. Figure 3 illustrates the HRSEM of the as-grown GaN film.…”
Section: Resultsmentioning
confidence: 94%
“…This value corresponds to the ionization energy of the generation level, which is attributed to the donor defect level introduced during the MOCVD growth. However, the high reverse dark current and the larger resistance observed in the device may be attributed to the density of dislocations remaining in the film [16,17]. Figure 3 illustrates the HRSEM of the as-grown GaN film.…”
Section: Resultsmentioning
confidence: 94%
“…Since hydrogen can act as a mobile space charge, we can intuitively expect an improvement in the leakage current when the hydrogen concentration is reduced inside p-GaN. The mechanism of the reverse leakage current in a GaN-based p-n junction is explained with a carrier hopping model and multi-step tunneling model [28][29][30]. Hydrogen can act as a defect itself, or cure the defect by the passivation of dangling bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have suggested that defects in particular dislocations might play an important role in the device characteristics [3][4][5][6]. The presence of bulk non-uniformities of shallow and deep centers as revealed by various techniques is the primary reason for the nonideal performance in high electric fields.…”
Section: Introductionmentioning
confidence: 99%